Cloud technologies for interaction and design learning - Mohamad, Nur Aziemah (2015)
Nowadays, engineering and applied science has complement with each other to make a new or improvement towards the technology. The technology has evolved from time to time and it has become an essential need for the human being in their daily life. Today, it is observed that most of the technologies are made to make the human life easier. The advancement of technology has also affected in the design field. Design is one of the basic components in creating an innovation, and yet it is a complex process to be done single-handedly. Thus, cloud computing may be useful in assisting the interaction in design process. Design has a vast definition and most of the time it is related to the architecture domain. Studio-based learning is a formal pedagogy for the future architects to learn about the domain. By having cloud implemented in the design learning, it gives opportunity for the designers to interact among each other. Therefore, in this paper, a focused on human-human interaction using cloud in assisting the design learning will be discussed accordingly.